2020
DOI: 10.3347/kjp.2020.58.6.609
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance on the Vivax Malaria in Endemic Areas in the Republic of Korea Based on Molecular and Serological Analyses

Abstract: <i>Plasmodium vivax</i> reemerged in 1993. It has been sustained for more than 25 years and become one of the important indigenous parasitic diseases in northern and western parts of the Republic of Korea near the demilitarized zone. In particular, relapse is a significant concern for the control of malaria, as short- and long-term incubation periods vary among those infected in Korea. In this study, the prevalence of asymptomatic carriers was examined among residents of high endemic areas of vivax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…It was commonly found that the inclusion of multiple Plasmodium antigens improved detection capacity [ 60 , 73 , 78 , 80 , 81 , 85 , 89 , 90 ]; however, mixed conclusions were drawn on the three most commonly used antigens. Pv MSP1-19 was deemed both useful [ 23 , 34 , 55 , 69 , 77 , 92 , 93 ] and uninformative [ 94 ] as an antigen to indicate exposure to P. vivax . Pv AMA1 was found to be both suitable [ 47 , 55 ] and ambiguous [ 94 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was commonly found that the inclusion of multiple Plasmodium antigens improved detection capacity [ 60 , 73 , 78 , 80 , 81 , 85 , 89 , 90 ]; however, mixed conclusions were drawn on the three most commonly used antigens. Pv MSP1-19 was deemed both useful [ 23 , 34 , 55 , 69 , 77 , 92 , 93 ] and uninformative [ 94 ] as an antigen to indicate exposure to P. vivax . Pv AMA1 was found to be both suitable [ 47 , 55 ] and ambiguous [ 94 ].…”
Section: Resultsmentioning
confidence: 99%
“…Kattenberg et al [ 63 ] found Pv AMA1 to only be useful for long-term changes in exposure, as opposed to identifying recent exposure. Pv CSP was deemed both apt [ 35 , 57 , 66 , 92 ] and imprecise [ 52 , 74 , 80 , 93 , 95 ] for the identification of P. vivax exposure. Other issues compounded this difficulty in antigen selection, including the existence of polymorphisms for some proteins [ 56 , 88 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Malaria is one of the oldest diseases, and its influence has probably been greater than that of any other infectious agents [ 5 ]. Caused by the Plasmodium species of protozoan parasites, malaria is a major public health burden worldwide [ 6 ]. P. falciparum is the most prevalent malaria parasite in Africa, and it is the greatest menace because of its high mortality rate [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…P. falciparum is the most prevalent malaria parasite in Africa, and it is the greatest menace because of its high mortality rate [ 7 ]. P. vivax is less lethal than P. falciparum , but more prevalent in Korea [ 6 ]. It was eradicated from Korea late 1970s, but re-emerged 1993 and continued prevalent despite the ongoing national eradication program [ 8 ].…”
Section: Introductionmentioning
confidence: 99%